Effect of Silibinin on Maspin and ERα Gene Expression in MCF-7 Human Breast Cancer Cell Line - Maryam Karimi; Hossein Babaahmadi-Rezaei; Ghorban Mohammadzadeh; Mohammad-Ali Ghaffari (Iranian Society of Pathology, 2017)
Background and objective: According to reports, a serine protease inhibitor (Maspin) suppresses metastasis, invasion and angiogenesis in breast and prostate cancers. Silibinin is a natural polyphenolic flavonoid with anti-cancer activity. We assessed the effects of silibinin on cell viability, maspin and ERα gene expression in MCF-7 cell line. Methods: The human MCF-7 breast cancer cell line was cultured in Dulbecco's Modified Eagle's Medium (DMEM) and treated with different concentrations of silibinin (100-600 μg/mL) for 24, 48 and 72 hours. The cytotoxic effect of silibinin on MCF-7 viability was determined using Methyl-Thiazolyl-Tetrazolium (MTT) assay by IC50 determination. The fold changes of Maspin and ERα expression were determined by reverse-transcription real-time Polymerase Chain Reaction (PCR). All experiments on the cells were performed in triplicates. Results: The maximum inhibitory effect of silibinin on cell viability was observed at 600 μg/mL after 72-hour incubation (p = 0.001). Incubation of the cells with silibinin for 48 and 72 hours significantly decreased IC50 values to 250 and 207 μg/mL (p = 0.005 and p= 0.006), respectively. The expression of maspin and ERα in the treated cells compared to controls was significantly decreased following treatment with different concentrations of silibinin during a 24-hour period. Conclusions: Silibinin reduces both maspin and ERα gene expression in MCF-7 cell line. The therapeutic effect of silibinin on the treatment of breast cancer may be mediated by the reduction of ERα expression. For verifying this hypothesis and the possible therapeutic implication of silibinin on breast cancer, further studies in this direction are necessary.